2012
DOI: 10.1080/03235408.2012.713799
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some mould inhibitors and herbal plants on mycotoxins production byAspergillus flavusandFusarium verticilloidesin vitro and in stored corn grains

Abstract: Clove oil, clove extract and butylated hydroxyanisole (BHA) completely suppressed the growth of both Fusarium verticilloides and Aspergillus flavus isolates. Black cumin and thyme extracts were more suppressive on F. verticilloides than A. flavus. Antitox-Plus (AP) had no effect on the growth of both the pathogens. The minimum inhibitory concentration (MIC) test revealed that A. flavus was more sensitive to Fix-A-Tox (FAT) and AP than F. verticilloides. In the growth media, all the tested substances, completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Vijayanadraj et al (2014) showed that the S. aromaticum aqueous extract reduced aflatoxin B1 by was 36.4%. Also,clove oil and clove extract completely inhibited aflatoxin production by A. flavus (Elsamra et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Vijayanadraj et al (2014) showed that the S. aromaticum aqueous extract reduced aflatoxin B1 by was 36.4%. Also,clove oil and clove extract completely inhibited aflatoxin production by A. flavus (Elsamra et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Then, incubation occurred at a pH value of 4.8 and a temperature of 25 °C for 24 h; 25 °C was the suitable temperature for S.indica growth 31 , and LAB metabolites have higher antiaflatoxigenic activity at a temperature of 25 °C 27 . Meanwhile, at a temperature of 25 °C, the production of the mycotoxin was the highest 44 . Three cylinders, 2000 ml each, were used in this experiment.…”
Section: Preparation Of Samples For Mycotoxins Detection Representatmentioning
confidence: 99%